Enhancing IPAS Learning through Inquiry-Based Learning Model at MIS Hamzanwadi Peneda - Majdi; Ahmad Taufik (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to investigate the impact of the Inquiry-Based Learning (IBL) model on students' understanding and engagement in Integrated Natural Sciences and Social Studies (IPAS) at MIS Hamzanwadi Peneda. IPAS is an essential subject that integrates natural sciences and social studies to provide students with a comprehensive understanding of their environment. However, traditional teaching methods often fail to fully engage students or foster critical thinking skills. The Inquiry-Based Learning model, which encourages students to ask questions, conduct investigations, and explore concepts actively, was chosen as an innovative approach to address these challenges. This research was conducted over two cycles, each involving planning, implementation, observation, and reflection. Data was collected through classroom observations, student assessments, and interviews with both teachers and students. The findings reveal that the implementation of IBL significantly improved students' engagement, curiosity, and problem-solving abilities in IPAS. By actively exploring real-world problems and conducting inquiries, students developed a deeper understanding of the topics studied, such as ecosystems, human impact on the environment, and basic scientific principles. Additionally, the model enhanced students' ability to think critically, collaborate with peers, and communicate their findings effectively. This research concludes that Inquiry-Based Learning is an effective approach to teaching IPAS, as it fosters active learning, critical thinking, and deeper understanding of scientific and social concepts. The study offers valuable insights for educators seeking to implement more engaging and student-centered teaching methods in the integrated sciences and social studies curriculum.